Progress on Light‐Emitting Electrochemical Cells toward Blue Emission, High Efficiency, and Long Lifetime. (16th February 2020) - Zhang, Chen; Liu, Ruihuan; Zhang, Dongdong; Duan, Lian
Abstract: Since their emergence in the 1990s, light‐emitting electrochemical cells (LECs) have attracted much attention due to their unique properties and potential for use as an alternative technology for illuminations and displays. After decades of development, however, the performance of LECs remains far from satisfactory for practical applications, in particular for those requiring blue light. Efforts have been made to develop of highly efficient blue‐emitting materials and more advanced device structures, aiming at realizing blueshifted emission, enhancing efficiency, and extending prolonged device lifetimes. A timely review into the current state of blue LECs is deemed imperative, as a full understanding of the molecular and device design strategy and identification of the major challenges that must be addressed to realize practical applications is necessary. A specific summary of recent progress on blue LECs is provided, with the focus placed on design strategies for blue emitters for LECs and device structures with respect to color tuning, efficiency enhancement, and stability improvement. Finally, the direction of development strategies in the future is suggested. Abstract : Recent progress in blue‐light‐emitting electrochemical cells is summarized. In particular, emitting active materials and device structures are explored in order to provide a comprehensive understanding to researchers in this field.